2001
DOI: 10.1021/ac010751z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Separation of the Enantiomers of 1-Phenyl-1-propanol on Cellulose Tribenzoate

Abstract: The competitive adsorption isotherms of rac-1-phenyl-1-propanol on cellulose tribenzoate were measured by competitive frontal analysis. The experimental data were fitted to four different isotherm models: Langmuir, Bilangmuir, Langmuir-Freundlich, and Tóth. The fittings of the experimental data to all four models were satisfactory. It was excellent in the case of the Langmuir-Freundlich and the Tóth models. Overloaded elution profiles calculated with the Tóth isotherm were in good agreement with the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…It is important to realize that the amount of the individual contributions, coming from the two types of sites (selective and non-selective), to the retention cannot be easily estimated by data measured under linear conditions. Only the determination of the equilibrium adsorption isotherms will allow the gathering of this information [54][55][56][57][58] and further investigations to fully clarify this point have been planned.…”
Section: Amino Acids-mehmentioning
confidence: 99%
“…It is important to realize that the amount of the individual contributions, coming from the two types of sites (selective and non-selective), to the retention cannot be easily estimated by data measured under linear conditions. Only the determination of the equilibrium adsorption isotherms will allow the gathering of this information [54][55][56][57][58] and further investigations to fully clarify this point have been planned.…”
Section: Amino Acids-mehmentioning
confidence: 99%
“…For example, in the case of adsorption of rac-1-phenyl-1-propanol on cellulose tribenzoate it has been shown that the extended version of the bL model, which accounts for the surface heterogeneity, gives more accurate predictions of the adsorption isotherms compared to the original bL model. 14 Similarly, it has been deduced from experimental data that lateral interactions may be responsible for some peculiarities observed in the adsorption isotherms. For example, strong attractive interactions may, in general, produce downward convexity of adsorption isotherms-unusual behavior that has been observed for different solutes including toluene and butyl benzene 20 or butyl benzoate.…”
Section: Introductionmentioning
confidence: 94%
“…Among them, the most prevalent are small groups (e.g., Pirkle phases) or macromolecules, including cellulose derivatives [13][14][15][16][17] and proteins. 18,19 Despite different physicochemical properties of various CSPs, enantioselective adsorption processes carried out in their presence are controlled by the same or very similar mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is essentially important for preparative chromatography to study the mass transfer phenomena in multi-component systems under non-linear isotherm conditions [2]. Cavazzini et al [110] studied the separation behavior of two enantiomers of 1-phenyl-1-propanol in a chromatographic system consisting of cellulose tribenzoate coated silica and a mixture of hexane and 2-propanol (97/3, v/v). It was reported that an increase in the concentration and injection volume of the sample solution of the racemic mixture is accompanied with an increase in the effective pore diffusion coefficient of S-1-phenyl-1-propanol.…”
Section: Gr Model With Generalized Maxwell -Stefan (Gms) Equationsmentioning
confidence: 99%